Damp-proof and anti-static carton production method

By preparing dual-function intelligent responsive ionic liquid and biological carrier composites, a multi-stage protective structure and dynamic hydrogen bond network are built, the problem of unstable moisture-proof and anti-static carton performance is solved, environmental adaptation and electrostatic self-healing are achieved, and high-demand packaging is suitable for high-demand packaging in electronics, pharmaceuticals and other industries.

CN120350573APending Publication Date: 2025-07-22YUN NAN HONG TA BAO ZHUANG SHI YE YOU XIAN ZE REN GONG SI

Patent Information

Application Number
CN202510303639.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-14
Publication Date
2025-07-22

AI Technical Summary

Technical Problem

The existing moisture-proof and anti-static cartons have single functions, fast performance attenuation, poor environmental protection, and cannot intelligently adjust the protection function according to environmental humidity, and lack self-repair capabilities, resulting in unstable protection effect under different storage and transportation conditions.

Method used

Dual-function intelligent responsive ionic liquid [HEIM][DCA/TFSI] is used to compound with chitosan and alginate to form a multi-stage protective structure. Moisture-proof and anti-static cartons are prepared through gradient drying, pressing and die-cutting processes, and humidity-sensitive ion distribution and dynamic hydrogen bonding network are built to achieve environmental adaptation and electrostatic self-healing.

Benefits of technology

It realizes the synergistic efficiency of moisture-proof and anti-static functions, and automatically adjusts the environment humidity according to the automatic adjustment function, has the ability to repair the static self-repair, provides all-round protection, improves the stability and durability of protective performance, and is suitable for packaging of environmentally sensitive items.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120350573A_ABST
    Figure CN120350573A_ABST
Patent Text Reader

Abstract

The invention discloses a moisture-proof and anti-static carton production method, and relates to the technical field of paper packaging materials, the method comprises the following steps: preparing a difunctional intelligent response type ionic liquid of 1-hydroxyethyl-3-methylimidazole cation [HEIM] and dicyandiamide / bis (trifluoromethanesulfonyl) imide mixed anion [DCA] / [TFSI]; respectively compounding the ionic liquid with chitosan and alginate to prepare a biological carrier compound; a functional paperboard containing a nano-pore network is constructed through paper pulp addition and surface coating; the electrostatic self-repairing structure is formed through gradient drying and three-section temperature control circulation treatment, environment self-adaptive adjustment is achieved through an intelligent response mechanism of the ionic liquid, and a multi-stage protection structure with a surface damp-proof layer, a middle-layer conductive network and an internal stable layer is formed; the device has the technical effects of dual-function synergistic interaction, intelligent humidity response, electrostatic self-repairing, selective molecular barrier and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of paper packaging materials, and specifically to a production method of a moisture-proof and anti-static carton. Background Art

[0002] With the rapid development of industries such as electronics, medicine, and precision instruments, the requirements for the moisture-proof and anti-static performance of packaging materials are increasing day by day. Traditional moisture-proof and anti-static cartons often have problems such as single function, rapid performance attenuation, and poor environmental protection, and there is an urgent need to develop new green packaging materials with multi-functional synergy.

[0003] The specification of Chinese invention patent CN111778758B discloses a waterproof and anti-static corrugated cardboard. Its production process includes batching, making pulp, making base paper, making cardboard, cardboard forming, and coating of a waterproof layer. The pulp includes the following components: premixed water, basic cellulose powder, added water, functional cellulose powder, silver powder, sodium hydroxide, cross-linking agent, and stabilizer. The waterproof layer coating includes the following components: waterborne polyurethane emulsion, functional cellulose powder, viscosity-adjusting water, and film-forming aid. The functional cellulose powder is glycine-grafted cellulose with a grafting rate of 1.5-3%. The corrugated cardboard made from the pulp of this application has good anti-static effect; the waterproof coating applied to the corrugated cardboard made from the pulp of this application can effectively achieve the waterproof function; the production method of the pulp of this application is relatively simple, and the obtained pulp is uniform and stable, which is beneficial to subsequent paper forming.

[0004] The specification of Chinese invention patent CN106638079B discloses a production method of pulp with anti-static characteristics, belonging to the technical field of pulp production, including the following steps: raw material selection, extrusion, soaking, cooking and sterilization, impurity removal, making pulp semi-finished product, making wet blank, making paper blank, making pulp finished product, and anti-static performance test. The present invention uses a new process to make anti-static pulp, and directly adds graphite fibers containing graphite and carbon black during the pulp processing to form conductive pulp, without the need to outsource the coating of a conductive layer during the process of manufacturing cartons, which not only simplifies the process but also reduces the cost. The pulp does not need to be outsourced for coating a conductive layer, and only needs to make anti-static pulp of the required model and specification, and corresponding anti-static cartons can be made according to requirements; it can act as an electrode to generate discharge, bring charges to the ground surface and air in time, and effectively improve the anti-static ability of the pulp, thus ensuring the safety of the product.

[0005] The above design realizes the waterproof and anti-static functions by adding functional components or coatings, but there are still certain limitations, such as: the moisture-proof and anti-static functions restrict each other, lacking environmental responsiveness; the use of traditional conductive materials such as silver powder, graphite, and carbon black has poor environmental friendliness and may affect the appearance of the cardboard box; the lack of self-healing function causes the anti-static performance to decay rapidly with the use time; the functional layer is easily peeled off due to external forces, resulting in the loss of performance. In addition, the existing technology cannot intelligently adjust the protection function according to the environmental humidity, and the protection effect is unstable under different storage and transportation conditions. Summary of the Invention

[0006] The purpose of the present invention is to overcome the deficiencies of the prior art and propose a production method for moisture-proof and anti-static cardboard boxes to solve the above existing problems.

[0007] The purpose of the present invention is achieved through the following technical solutions: A production method for moisture-proof and anti-static cardboard boxes, comprising the following steps: S1: Prepare a bifunctional intelligent-responsive ionic liquid, the ionic liquid contains 1-hydroxyethyl-3-methylimidazolium cation [HEIM]⁺ and a mixed anion of dicyanimide / bis(trifluoromethanesulfonyl)imide [DCA]⁻ / [TFSI]⁻, wherein the molar ratio of [DCA]⁻ / [TFSI]⁻ is 5:1 to 9:1; S2: Compound the ionic liquid with chitosan and alginate respectively to prepare a first biological carrier complex and a second biological carrier complex; S3: Add the first biological carrier complex to the pulp to form a basic cardboard by papermaking, and coat the second biological carrier complex on the surface of the cardboard to form a moisture-proof and anti-static functional layer; S4: Gradient dry, press, and die-cut the cardboard to make a moisture-proof and anti-static cardboard box.

[0008] Step S1 includes: S11: React biobased methylimidazole and biobased hydroxyethyl chloride in a system with a pH of 8.0 - 9.0, preferably using immobilized lipase (Novozyme 435, reference Biotechnol. Lett., 2019, 41:123 - 131) or potassium hydroxide as a catalyst, at 35 - 45 °C for 8 - 12 hours to generate 1-hydroxyethyl-3-methylimidazolium chloride; S12: After centrifuging (6000 rpm, 15 minutes) the product of step S11 to separate the catalyst, mix it with lithium dicyanimide and lithium bis(trifluoromethanesulfonyl)imide according to a predetermined molar ratio, and perform an ultrasonic-assisted reaction in acetonitrile / water (volume ratio 2:1 to 4:1, total salt concentration 0.2 - 0.5 mol / L) at 20 - 50 kHz for 30 - 60 minutes; S13: Centrifuge the reaction solution successively, purify it by organic solvent / water two-phase extraction, and freeze-dry it for 12 - 36 hours to obtain the [HEIM][DCA / TFSI] ionic liquid with a purity of not less than 95%.

[0009] Step S2 includes: S21: Dissolve the modified chitosan in a 1 - 3% acidic solution, mix it with the ionic liquid in a mass ratio of 1:1 to 1:3, add 3 - 8% polyvinylpyrrolidone as a compatibilizer, and stir at 50 - 70°C for 2 - 4 hours to prepare the first biocarrier complex; S22: Mix alginate with the ionic liquid in a ratio of 1:1 to 1:2, add 5 - 10% non-ionic crosslinking agent, and add 1 - 5% nano-reinforcing agent, and crosslink at room temperature for 4 - 6 hours to prepare the second biocarrier complex.

[0010] Step S3 includes: S31: Add the first complex to the pulp (pH 6.5 - 7.5) at 1 - 3%, and simultaneously add 0.5 - 1.5% carboxymethyl cellulose and 0.2 - 0.5% cationic starch; S32: Use segmented vacuum dewatering during papermaking, with an initial negative pressure of 10 - 15 kPa and a final negative pressure of 20 - 25 kPa; S33: Mix the second complex with 15 - 25% polyethylene glycol templating agent (molecular weight 6,000 - 12,000), adjust the viscosity according to the coating method, and apply it to the surface of the cardboard, with a coating amount of 30 - 80 g / m²; S34: Immerse the coated cardboard in an alkaline solution with a pH of 8.5 - 10.0 for 8 - 15 minutes, immediately rinse it with a weak acid solution (pH 4.0 - 5.5) for 5 - 15 seconds for neutralization, and then rinse it thoroughly with deionized water to form a nanoporous network with a pore size of 20 - 50 nm.

[0011] Step S4 includes: S41: Dry at a heating rate of 0.5 - 1.5°C / minute to 50 - 60°C for 15 - 25 minutes, and then dry at 70 - 80°C for 10 - 20 minutes; S42: Under a pressure of 0.5 - 1.5 MPa, hot-press at 55 - 70°C for 1 - 3 minutes (adjust the temperature according to the cardboard thickness and fiber composition), cool to 35 - 45°C at a rate not exceeding 3°C / minute, and then equilibrate in an environment with a relative humidity of 40 - 60% for 4 - 6 hours; S43: Die-cut the treated cardboard to make a moisture-proof and anti-static carton.

[0012] Form a multi-level protection structure through the following steps: S61: Add 0.5 - 1.5% of amino - modified fluorosilane surface energy regulator (such as N-(3 - trimethoxysilylpropyl)ethylenediamine) to the coating solution, control the coating speed at 6 - 10 m / min, and promote the directional migration of [TFSI]⁻ to the surface through the surface energy gradient formed during the solvent evaporation process; S62: Add 0.5 - 1.5% of carboxymethyl cellulose and 0.2 - 0.4% of cationic starch to the pulp, control the beating degree at 30 - 40°SR, and promote the formation of a continuous conductive network of [DCA]⁻ in the middle layer; S63: Control the pulp temperature at 30 - 40°C, the stirring speed at 150 - 200 rpm, and add 0.2 - 0.5% of dispersant to improve the uniform distribution of ionic liquid complexes between fibers.

[0013] The humidity response is achieved through the following steps: S71: Control the molar ratio of [DCA]⁻ / [TFSI]⁻ at 6:1 to 8:1 in step S1; S72: Add 3 - 8% of polydimethylsiloxane (viscosity 500 - 2000 cSt) and 2 - 5% of polyether - modified polysiloxane as compatibilizers in step S22, and use ultrasonic dispersion for pre - mixing treatment for 10 - 15 minutes to ensure uniform dispersion of components; S73: Control the coating thickness at 15 - 25 μm, the density at 0.8 - 1.2 g / cm³, and implement slow gradient drying in step S41 to form a humidity - sensitive ionic distribution structure.

[0014] The electrostatic self - repair is achieved through the following steps: S81: Add 5 - 10% of partially hydrophobic - modified polyvinyl alcohol (acetylation degree 5 - 15%, molecular weight 85,000 - 120,000) in step S21; S82: First add 1 - 3% of multi - functional isocyanate cross - linker in step S22 to pre - react with alginate for 30 - 60 minutes, and then add 3 - 5% of glycerol and 1 - 3% of tributyl citrate as a mixed plasticizer; S83: Adopt a two - stage temperature - controlled cycle in step S42: heat from room temperature to 65 - 70°C at a rate of 2 - 3°C / min and hold for 60 - 90 seconds, then cool to 35 - 40°C at a rate of 2 - 3°C / min and hold for 60 seconds, repeat once, and control the total time within 5 minutes to efficiently form a dynamic hydrogen - bond network.

[0015] In step S3, adjust the process parameters according to different coating methods: S91: When doctor - blading, control the viscosity of the coating solution at 500 - 1000 mPa·s and the doctor - blade gap at 100 - 200 μm; S92: During spraying, the viscosity of the coating liquid is controlled at 100 - 250 mPa·s (the fluidity can be adjusted by adding 5 - 10% ethanol or isopropanol), the spraying pressure is 0.2 - 0.4 MPa, and the nozzle distance is 150 - 250 mm; S93: During dipping, the viscosity of the coating liquid is controlled at 300 - 600 mPa·s, the dipping time is 15 - 45 seconds, and the pulling speed is 3 - 8 mm / s.

[0016] The beneficial effects of the present invention are as follows: 1. Through the mixing anion ratio of [HEIM]⁺ with [DCA]⁻ / [TFSI]⁻, the present invention realizes the functions of moisture-proof and anti-static, achieves the synergistic effect of the two functions, and makes the moisture-proof performance and anti-static performance promote each other rather than restrict each other.

[0017] 2. The humidity-sensitive ion distribution structure constructed by the present invention can automatically adjust its function according to the change of environmental humidity. In a high-humidity environment, the [DCA]⁻ anion channel is activated to enhance static dissipation, and in a low-humidity environment, the [TFSI]⁻ anion forms a dense moisture-proof barrier, realizing the environmental self-adaptability of the carton protection function.

[0018] 3. Through the construction of a dynamic hydrogen bond network and a three-stage temperature control cycle process, the present invention endows the carton with the ability to automatically repair the conductive channel after being damaged, improves the persistence and stability of the anti-static performance, and solves the technical problem of the easy attenuation of the performance of traditional anti-static cartons.

[0019] 4. The present invention adopts a spatial partition design of a surface moisture-proof layer, a middle conductive network, and an internal stable layer, realizes the optimal distribution of functional components, avoids the mutual interference between different functions, forms a synergistic overall protection system, and provides all-round protection.

[0020] 5. Through the nano-channel network constructed by a soluble templating agent, a selective barrier is formed, which can block the penetration of water molecules while promoting the directional migration of ions and static dissipation, and solves the contradiction between the moisture-proof and conductive functions from the micro-structure. Description of the Drawings

[0021] Figure 1 For the preparation steps of the present invention Figure 1 ; Figure 2 For the preparation steps of the present invention Figure 2 。 Detailed Embodiments

[0022] The technical solutions of the present invention will be clearly and completely described below in conjunction with embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative efforts belong to the scope of protection of the present invention.

[0023] It should be noted that in the following solutions, the orientation concepts of "left", "right", "up", "down", "front", "back", "inside", and "outside" are all relative directions, and will not be listed one by one here.

[0024] Embodiment 1 As Figure 1 and Figure 2 shown, this embodiment provides a method for producing a moisture-proof and anti-static carton. This method realizes the moisture-proof and anti-static functions of the carton by preparing a bifunctional intelligent responsive ionic liquid, combining it with a biological carrier material to form a functional composite, and applying it to the carton production process.

[0025] S1: Prepare a bifunctional intelligent responsive ionic liquid S11: Synthesize 1-hydroxyethyl-3-methylimidazolium chloride React biobased methylimidazole and biobased chloroethanol in a system with a pH of 8.5, using immobilized lipase Novozyme 435 as a catalyst, at 40 °C for 10 hours to generate 1-hydroxyethyl-3-methylimidazolium chloride. Control the substrate concentration in the reaction system to be 0.3 mol / L, and the catalyst dosage to be 5% of the total mass of the substrate. At the same time, maintain gentle stirring of the reaction system to ensure sufficient contact.

[0026] S12: Anion exchange reaction After separating the catalyst from the product of step S11 by centrifugation (6000 rpm, 15 minutes), mix it with lithium dicyanimide and lithium bis(trifluoromethanesulfonyl)imide in a molar ratio of 7:1, and react under ultrasonic assistance at 30 kHz for 45 minutes in acetonitrile / water (volume ratio 3:1, total salt concentration 0.35 mol / L). The ultrasonic treatment is carried out under a water bath condition, and the temperature is controlled not to exceed 45 °C to avoid degradation of the ionic liquid.

[0027] S13: Purify the ionic liquid First, centrifuge the reaction solution (8000 rpm, 20 minutes) to remove insoluble impurities, and then perform three purifications by dichloromethane / water two-phase extraction. Collect the organic phase, remove the organic solvent by rotary evaporation, and then freeze-dry the aqueous phase at -50 °C for 24 hours to obtain [HEIM][DCA / TFSI] ionic liquid with a purity of 97%. The final product is a light yellow viscous liquid with good fluidity and stability.

[0028] S2: Prepare the bio-carrier complex S21: Prepare the first bio-carrier complex Dissolve the modified chitosan with a deacetylation degree of 85% in a 2% acetic acid solution to form a uniform solution with a concentration of 3%. Mix it with the ionic liquid at a mass ratio of 1:2. At the same time, add 5% polyvinylpyrrolidone (molecular weight about 40,000) as a compatibilizer. Stir the mixture at 60°C for 3 hours to ensure that all components are fully and evenly mixed, and obtain the first bio-carrier complex with good compatibility.

[0029] S22: Prepare the second bio-carrier complex Mix medium-viscosity sodium alginate with the ionic liquid at a mass ratio of 1:1.5. Add 7% epoxy multi-arm polyethylene glycol as a non-ionic cross-linking agent, and add 3% nanocellulose as a reinforcing agent. After mechanically stirring and ultrasonically dispersing the mixture at room temperature (about 23°C), let it stand for cross-linking for 5 hours to obtain the second bio-carrier complex, which has excellent film-forming properties and elasticity.

[0030] S3: Prepare the functional cardboard S31: Pulp preparation Add the first complex to the mixed pulp of softwood sulfate pulp and hardwood pulp (ratio 7:3) at 2%. Adjust the pH to 7.0. At the same time, add 1% carboxymethyl cellulose and 0.3% cationic starch as strengthening and retention agents. In the pulp preparation stage, control the pulp concentration at 0.5%, and use a high-shear mixer to ensure that the complex is evenly dispersed in the fiber network.

[0031] S32: Stepwise dewatering Use a Fourdrinier paper machine for forming, and adopt a stepwise vacuum dewatering process. Set the negative pressure at 12 kPa in the initial stage, gradually increase it to 18 kPa in the middle stage, and set the negative pressure at 22 kPa in the final stage. Through this gradient dewatering method, ensure that the ionic liquid complex is evenly distributed in the paper structure, while maintaining the formation and strength of the paper.

[0032] S33: Surface coating Mix the second complex with 20% polyethylene glycol templating agent (molecular weight 10,000), adjust the viscosity to 3000 - 3500 mPa·s, and apply it to the surface of the cardboard using an air knife coater. Control the coating amount at 60 g / m², and maintain a constant tension of the cardboard during the coating process to ensure the uniformity of the coating.

[0033] S34: Form a nano-pore network The coated cardboard was soaked in a sodium carbonate solution with a pH of 9.0 for 12 minutes, then immediately rinsed with an acetic acid solution with a pH of 4.5 for 10 seconds for neutralization, and then thoroughly rinsed with deionized water three times. Finally, it was pre-dried at room temperature for 10 minutes. This treatment process formed a nanoporous network structure with an average pore size of 35 nm in the cross-linked ionic liquid composite.

[0034] S4: Cardboard forming and processing S41: Gradient drying A multi-stage dryer was used to heat up to 55 °C at a heating rate of 1.0 °C per minute and dry for 20 minutes, and then heat up to 75 °C and continue drying for 15 minutes. This gradient drying method can reduce cardboard deformation and ensure the integrity of the ionic liquid functional layer.

[0035] S42: Pressing and humidity conditioning Under a pressure of 1.0 MPa, it was hot-pressed at 65 °C for 2 minutes, and then cooled to 40 °C at a rate of 2 °C per minute. During the hot-pressing process, a smooth mirror pressing plate was used to ensure the flatness of the cardboard surface. After pressing, the cardboard was placed in an environment with a relative humidity of 50% and a temperature of 23 °C for 5 hours to fully release the internal stress of the cardboard and improve the dimensional stability.

[0036] S43: Die-cutting and forming According to the design requirements, a computer-controlled precision die-cutting machine was used to die-cut, score, and form the processed cardboard to obtain a finished moisture-proof and anti-static cardboard box. During the die-cutting process, the tool pressure and cutting speed were controlled to ensure neat cut edges, appropriate creases, and no damage to the functional coating.

[0037] First, a bifunctional intelligent responsive ionic liquid [HEIM][DCA / TFSI] with a specific cation-anion ratio was synthesized from bio-based raw materials. This ionic liquid has a unique chemical structure. The hydroxyl functional group and the imidazole ring structure provide good biocompatibility, while the [DCA]⁻ / [TFSI]⁻ mixed anions provide excellent moisture-proof and conductive properties.

[0038] The synthesized ionic liquid was respectively compounded with chitosan and alginate to form two different functional bio-carrier composites. The chitosan composite mainly provides structural strength and internal moisture-proof function; the alginate composite mainly provides surface anti-static function and physical barrier.

[0039] During the cardboard box production process, the first composite was uniformly distributed inside the cardboard by adding it to the pulp, and the second composite was formed into a functional coating by surface coating. Through soaking and neutralization treatment, a nanoporous network was formed in the coating, improving the ion migration ability and responsiveness.

[0040] Finally, through precisely controlled drying, pressing, and humidity conditioning processes, the physical properties and functional stability of the cardboard are ensured. Then, through die-cutting and forming, the final moisture-proof and anti-static carton products are obtained.

[0041] The ionic liquid synthesized from bio-based raw materials is environmentally friendly and safe, reducing the environmental impact of the production process and the final product, and conforming to the development trend of green packaging.

[0042] The bifunctional intelligent-responsive ionic liquid has a reasonable structure design. Through the synergistic effect of [DCA]⁻ / [TFSI]⁻ mixed anions, the organic unity of moisture-proof and anti-static functions is achieved, and it has better comprehensive performance compared with single-functional ionic liquids.

[0043] Chitosan and alginate, as biological carriers, form a stable composite system with the ionic liquid, enhancing the fixation and persistence of the ionic liquid in the cardboard and preventing the loss and migration of functional components.

[0044] The layered application strategy (internal addition and surface coating) realizes the differential design of the functions inside and outside the carton. The inside is mainly moisture-proof, and the outside is mainly anti-static, making the resource utilization more efficient.

[0045] The construction of the nanoporous channel network structure improves the environmental responsiveness of the ionic liquid. It can actively adjust the water absorption and release when the humidity changes, and can effectively conduct charges when the electrostatic environment changes, protecting the items inside the package from humidity and static damage.

[0046] The gradient drying and pressing processes reduce the internal stress of the cardboard, improve the dimensional stability and service life of the carton, and at the same time maintain good folding performance and compressive strength.

[0047] The overall production process is compatible with the existing carton production line and can be realized with only a small amount of equipment modification, having good industrial application prospects.

[0048] Compared with traditional moisture-proof and anti-static cartons, the cartons produced by this method have significantly improved moisture-proof and anti-static effects while maintaining good physical and mechanical properties, and are particularly suitable for the packaging and transportation of environmentally sensitive items such as electronic components, precision instruments, and pharmaceutical products.

[0049] Example 2 As Figure 1 and Figure 2 shown, based on Example 1, in this example, by optimizing the ionic liquid ratio, introducing a surface energy regulation mechanism, and constructing a multi-level protection structure, the moisture-proof and anti-static performance and its environmental responsiveness of the carton are further improved.

[0050] S1: Preparation of bifunctional intelligent-responsive ionic liquid S11: Synthesis of 1-hydroxyethyl-3-methylimidazolium chloride Using the same method as in Example 1, bio-based methylimidazole and bio-based 2-chloroethanol were reacted in a system with a pH of 8.5 using immobilized lipase Novozyme 435 as a catalyst at 40 °C for 10 hours to produce 1-(2-hydroxyethyl)-3-methylimidazolium chloride. During the reaction, the stirring speed was controlled at 120 rpm to ensure sufficient contact between the reactants without causing mechanical damage to the enzyme activity.

[0051] S12: Anion exchange reaction After separating the catalyst from the product of step S11 by centrifugation (6000 rpm, 15 minutes), it was mixed with lithium dicyanamide and lithium bis(trifluoromethanesulfonyl)imide in a molar ratio of 7.5:1 (implementing S71, controlling the molar ratio of [DCA]⁻ / [TFSI]⁻ within the range of 6:1 to 8:1). In acetonitrile / water (volume ratio 3:1, total salt concentration 0.35 mol / L), the reaction was assisted by ultrasound at 30 kHz for 45 minutes, and the ultrasound was paused for 1 minute every 15 minutes to prevent the temperature from being too high and affecting the product stability.

[0052] S13: Purifying the ionic liquid The reaction solution was first centrifuged (8000 rpm, 20 minutes) to remove insoluble impurities, and then purified three times by ethyl acetate / water two-phase extraction. The organic phase was collected, and the organic solvent was removed by rotary evaporation. The product was freeze-dried at -50 °C for 24 hours to obtain [HEIM][DCA / TFSI] ionic liquid with a purity of 98%. The product was confirmed by ultraviolet spectrophotometer and infrared spectroscopy, showing the expected ionic characteristic absorption peaks.

[0053] S2: Preparing the bio-carrier complex S21: Preparing the first bio-carrier complex The modified chitosan with a degree of deacetylation of 90% was dissolved in a 2% acetic acid solution to form a homogeneous solution with a concentration of 3%. It was mixed with the ionic liquid in a mass ratio of 1:2, and 5% polyvinylpyrrolidone was added as a compatibilizer. The mixture was stirred at 60 °C for 3 hours to ensure sufficient mixing of all components, and the first bio-carrier complex was prepared. During the preparation process, a combination of mechanical stirring and intermittent ultrasound was used to improve the uniformity of the complex.

[0054] S22: Preparing the second bio-carrier complex Mix medium-viscosity sodium alginate with ionic liquid at a mass ratio of 1:1.5, add 7% epoxy-functionalized multi-arm polyethylene glycol as a non-ionic crosslinker, and add 3% nanocellulose as a reinforcing agent. Implementation of S72: Add 5% polydimethylsiloxane (viscosity 1000 cSt) and 3% polyether-modified polysiloxane as compatibilizers simultaneously, and perform ultrasonic dispersion premixing treatment at a power of 300 W for 12 minutes to ensure uniform dispersion of components. Subsequently, let it stand and crosslink at room temperature (about 23 °C) for 5 hours to obtain the second biological carrier complex. The ultrasonic treatment in this step is intermittent (working for 2 minutes and pausing for 30 seconds) to avoid material degradation caused by local overheating.

[0055] S3: Prepare functional cardboard S31: Pulp preparation Add the first complex to the mixed pulp of softwood sulfate pulp and hardwood pulp (ratio 6:4) at 2%, adjust the pH to 7.0. Implementation of S62: Add 1% carboxymethyl cellulose and 0.3% cationic starch simultaneously, control the beating degree at 35 °SR to promote the formation of a continuous conductive network of [DCA]⁻ in the middle layer of the cardboard. Implementation of S63: Control the pulp temperature at 35 °C and the stirring speed at 180 rpm, add 0.3% sodium polyacrylate as a dispersant to improve the uniform distribution of the ionic liquid complex among the fibers. During the pulp preparation process, adopt a segmented addition method. First, fully mix the dispersant with the pulp, then slowly add the functional complex, and finally add the retention agent system.

[0056] S32: Segmented dewatering Use a Fourdrinier paper machine for forming, adopt a segmented vacuum dewatering process. Set the negative pressure at 12 kPa in the initial section, gradually increase it to 18 kPa in the middle section, and set the negative pressure at 22 kPa in the final section. Control the vibration frequency in the paper forming area during the dewatering process to promote the uniform distribution of fibers and functional complexes, and at the same time avoid the loss of functional components with water.

[0057] S33: Surface coating Implementation of S61: Add 1% amino-modified fluorosilane surface energy regulator N-(3-trimethoxysilylpropyl)ethylenediamine to the second complex, mix it with 20% polyethylene glycol template agent (molecular weight 10,000), adjust the viscosity to 3000 - 3500 mPa·s, and apply it to the cardboard surface using an air knife coater. Control the coating speed at 8 m / min and the coating amount at 60 g / m². The control of this speed enables the formation of a surface energy gradient during the solvent evaporation process, promotes the directional migration of [TFSI]⁻ to the surface, and enhances the surface antistatic effect. Implementation of S73: Control the coating thickness at 20 μm and the density at 1.0 g / cm³ to prepare for the subsequent formation of a humidity-sensitive ionic distribution structure.

[0058] S34: Form a nanopore network The coated cardboard was soaked in a sodium carbonate solution with a pH of 9.0 for 12 minutes, then immediately rinsed with an acetic acid solution with a pH of 4.5 for 10 seconds for neutralization, and then thoroughly rinsed with deionized water three times. Finally, it was pre-dried at room temperature for 10 minutes. During this process, partial cross-linking occurred between the amino-modified fluorosilane and the alginate, forming a surfactant nanostructure, which further enhanced the moisture-proof and anti-static properties of the functional coating.

[0059] S4: Cardboard forming and processing S41: Gradient drying Implementation of S73: A multi-stage dryer was used to implement slow gradient drying. The temperature was raised to 55 °C at a heating rate of 0.7 °C / minute and dried for 25 minutes, and then raised to 75 °C at a heating rate of 0.8 °C / minute and continued to dry for 15 minutes. This slow gradient drying method promoted the formation of a humidity-sensitive layered structure of the ionic liquid in the coating, making the [DCA]⁻ ions tend to aggregate in the inner layer, while the [TFSI]⁻ ions were more distributed on the surface layer, forming a responsive gradient structure.

[0060] S42: Pressing and humidity conditioning Under a pressure of 1.0 MPa, it was hot-pressed at 65 °C for 2 minutes, and then cooled to 40 °C at a rate of 1.5 °C / minute. During the hot-pressing process, a micro-textured pressing plate was used to provide moderate surface roughness and enhance the anti-slip performance. After pressing, the cardboard was placed in an environment with a relative humidity of 55% and a temperature of 23 °C for 5 hours to fully release the internal stress of the cardboard and improve the dimensional stability. By controlling the pressing parameters, it was ensured that the ionic liquid functional layer obtained appropriate density while maintaining the original structure.

[0061] S43: Die-cutting and forming According to the design requirements, a computer-controlled precision die-cutting machine was used to die-cut, score, and form the processed cardboard to obtain a moisture-proof and anti-static cardboard box product. The die-cutting tool used a chrome-plated die to reduce damage to the functional coating during the cutting process. After forming, the cardboard box was conditioned in a constant temperature and humidity environment for 24 hours to ensure the stability of the humidity-responsive structure before use.

[0062] First, a bifunctional intelligent responsive ionic liquid [HEIM][DCA / TFSI] with an optimized ratio was synthesized from bio-based raw materials, where the molar ratio of [DCA]⁻ / [TFSI]⁻ was controlled at 7.5:1. This ratio was precisely adjusted to enable the ionic liquid to simultaneously possess excellent moisture-proof performance and moderate static conductivity, laying a foundation for the subsequent construction of a humidity-responsive structure.

[0063] The synthesized ionic liquids were respectively compounded with chitosan and alginate to form functional complexes. During the preparation of the second biological carrier complex, polydimethylsiloxane and polyether-modified polysiloxane were introduced as compatibilizers. Through ultrasonic dispersion and premixing treatment, the components were ensured to be evenly dispersed, improving the stability and functionality of the complexes.

[0064] During the production process of cartons, a multi-level protection structure strategy was implemented: a dispersant was added to the pulp to control the temperature and stirring speed, promoting the uniform distribution of the ionic liquid complex among the fibers; the beating degree was controlled to form a continuous conductive network of [DCA]⁻ in the middle layer; an amino-modified fluorosilane surface energy regulator was added to the coating solution and the coating speed was controlled to promote the directional migration of [TFSI]⁻ to the surface, forming a protective layer with a gradient structure.

[0065] By controlling the slow gradient drying to control the distribution of ions in the coating, a humidity-sensitive ionic distribution structure was formed. This structure can undergo structural reorganization when the humidity changes, providing a dynamic moisture-proof and anti-static response. Finally, through precisely controlled pressing and die-cutting processes, a moisture-proof and anti-static carton product with a multi-level protection structure and humidity response function was produced.

[0066] By controlling the molar ratio of [DCA]⁻ / [TFSI]⁻ within the optimized range (7.5:1), the balance between the moisture-proof performance and electrostatic conductivity of the ionic liquid was achieved, enabling the carton to maintain a stable protective effect under different environmental conditions.

[0067] An amino-modified fluorosilane surface energy regulator was added to the coating solution. By utilizing the surface energy gradient, the directional migration of [TFSI]⁻ to the surface was promoted, forming an efficient anti-static surface layer while maintaining the internal moisture-proof function, realizing the spatial differentiation of functions.

[0068] By controlling the beating degree, temperature of the pulp and adding a dispersant, the formation of a continuous conductive network of [DCA]⁻ in the middle layer was promoted, enhancing the overall moisture-proof performance and mechanical strength of the carton and improving the service life of the product.

[0069] Polydimethylsiloxane and polyether-modified polysiloxane were added as compatibilizers, improving the compatibility between the ionic liquid and the biological carrier, reducing the phase separation phenomenon, and enhancing the stability and durability of the functional material.

[0070] The slow gradient drying process was implemented to form a humidity-sensitive ionic distribution structure, enabling the carton to actively adjust its protective performance according to environmental humidity changes, strengthening the moisture-proof effect in high-humidity environments and enhancing the anti-static function in dry environments, realizing an intelligent response.

[0071] The constructed multi-level protection structure endows the carton with a hierarchical protection mechanism: the surface layer mainly provides anti-static and physical barrier functions, the middle layer provides moisture-proof and structural support functions, and the inner layer protects the items inside the package from external environmental interference, forming a three-dimensional protection system.

[0072] Ultrasonic dispersion pre-mixing treatment ensures the uniform dispersion of the composite components, reduces material defects and performance inhomogeneity, and improves the consistency and reliability of product quality.

[0073] The use of amino-modified fluorosilane not only enhances the anti-static performance but also provides a certain degree of hydrophobicity, enhancing the structural stability and strength retention rate of the carton in high-humidity environments and expanding the application environment range of the product.

[0074] The optimized pressing and humidity conditioning processes reduce the internal stress in the cardboard, improve the dimensional stability and folding performance of the carton, and at the same time maintain the integrity and activity of the functional layer, ensuring that the functions do not decay during long-term use.

[0075] Although the overall production process adds several key control points, it is still compatible with the existing carton production line, has a higher input-output ratio, and has better economic benefits and promotion value.

[0076] Example 3 As Figure 1 and Figure 2 shown, based on Examples 1 and 2, this example realizes the electrostatic self-repair function of the carton and the process optimization of multiple coating methods by adding specific components and adjusting process parameters, further improving product performance and production flexibility.

[0077] S1: Prepare a bifunctional intelligent responsive ionic liquid S11: Synthesize 1-hydroxyethyl-3-methylimidazolium chloride Same as Example 1, react biobased methylimidazole with biobased hydroxyethyl chloride in a system with pH 8.5, using immobilized lipase Novozyme 435 as a catalyst, react at 40 °C for 10 hours to generate 1-hydroxyethyl-3-methylimidazolium chloride. During the reaction process, use a magnetic stirrer for uniform stirring to ensure the uniform dispersion and full contact of the reactants.

[0078] S12: Anion exchange reaction After separating the catalyst from the product of step S11 by centrifugation (6000 rpm, 15 minutes), mix it with lithium dicyanimide and lithium bis(trifluoromethanesulfonyl)imide in a molar ratio of 8:1, and react in acetonitrile / water (volume ratio 3:1, total salt concentration 0.35 mol / L) with ultrasonic assistance at 30 kHz for 45 minutes. The ultrasonic treatment adopts an intermittent mode (working for 30 seconds and pausing for 10 seconds) to prevent side reactions caused by excessive temperature in the reaction system.

[0079] S13: Purify the ionic liquid Centrifuge the reaction solution (8000 rpm, 20 minutes) to remove insoluble impurities. Subsequently, perform three purifications using dichloromethane / water two-phase extraction. Collect the organic phase. After removing the organic solvent by rotary evaporation, lyophilize the aqueous phase at -50 °C for 24 hours to obtain the [HEIM][DCA / TFSI] ionic liquid with a purity of 97%. During the purification process, control the rotary evaporation temperature not to exceed 40 °C to avoid damage to the ionic liquid structure caused by high temperature.

[0080] S2: Prepare the biocarrier composite S21: Prepare the first biocarrier composite Implementation of S81: Dissolve the modified chitosan with a degree of deacetylation of 85% in a 2% acetic acid solution to form a homogeneous solution with a concentration of 3%. Add 7% partially hydrophobic modified polyvinyl alcohol (acetylation degree 10%, molecular weight 100,000), mix it with the ionic liquid at a mass ratio of 1:2, and simultaneously add 5% polyvinylpyrrolidone as a compatibilizer. Stir the mixture at 60 °C for 3 hours to ensure that all components are fully mixed evenly, and obtain the first biocarrier composite. The partially hydrophobic modified polyvinyl alcohol added in this step can form semi-crystalline regions to provide charge storage space when the electrostatic conditions change.

[0081] S22: Prepare the second biocarrier composite Implementation of S82: First, pre-react 2% of the polyfunctional isocyanate crosslinker (trimethylolpropane triisocyanate) with medium-viscosity sodium alginate under gentle stirring for 45 minutes to form a partially crosslinked network structure. Subsequently, add the ionic liquid, mix it at a mass ratio of alginate to ionic liquid of 1:1.5, and then add 4% glycerol and 2% tributyl citrate as a mixed plasticizer, as well as 3% nanocellulose as a reinforcing agent. After mechanically stirring and ultrasonically dispersing the mixture at room temperature (about 23 °C), let it stand for crosslinking for 5 hours to obtain the second biocarrier composite. The addition of the mixed plasticizer provides moderate segmental mobility to ensure that ions can rearrange under the action of an electric field.

[0082] S3: Prepare the functional cardboard S31: Pulp preparation Add the first composite to the mixed pulp of softwood sulfate pulp and hardwood pulp (ratio 7:3) at 2%, adjust the pH to 7.0, and simultaneously add 1% carboxymethyl cellulose and 0.3% cationic starch as strengthening and retention agents. During the pulp preparation stage, control the pulp concentration to 0.5%, and ensure the uniform dispersion of the composite in the fiber network through a high-shear mixer. The first composite added to the pulp contains partially hydrophobic modified polyvinyl alcohol, which can form a micro-region electrostatic shielding network inside the cardboard.

[0083] S32: Stagewise dewatering Use a Fourdrinier paper machine for forming, adopt a stagewise vacuum dewatering process, set a negative pressure of 12 kPa in the initial stage, gradually increase it to 18 kPa in the middle stage, and set the negative pressure in the final stage to 22 kPa. Control the dewatering rate during the stagewise dewatering process to ensure that the functional composite can be fully combined on the fiber surface to form a uniform protective layer.

[0084] S33: Surface coating Adjust the coating parameters according to different coating methods: Implementation of S91: When using the knife coating method, adjust the viscosity of the second composite to 750 mPa·s, set the knife coating gap to 150 μm, control the knife coating speed at 12 m / min, and use a 45° knife coating angle during knife coating to ensure the uniformity of the coating.

[0085] Implementation of S92: When using the spraying method, adjust the viscosity of the second composite to 200 mPa·s by adding 7% isopropyl alcohol, set the spraying pressure to 0.3 MPa, the nozzle distance to 200 mm, and adopt a multi-pass cross-spraying method during spraying to ensure uniform coverage of the coating.

[0086] Implementation of S93: When using the dipping method, adjust the viscosity of the second composite to 450 mPa·s, immerse the cardboard for 30 seconds, control the pulling speed at 5 mm / s, and use ultrasonic assistance during immersion to improve the liquid penetration efficiency.

[0087] The coating amount under different coating methods is controlled at 60 g / m² to ensure the performance consistency of the functional coating.

[0088] S34: Form a nanopore network Immerse the coated cardboard in a sodium carbonate solution with a pH of 9.0 for 12 minutes, then immediately rinse it with an acetic acid solution with a pH of 4.5 for 10 seconds for neutralization, then rinse it thoroughly with deionized water 3 times, and finally pre-dry it at room temperature for 10 minutes. The nanopore network formed during this process has a specific surface charge distribution, which helps the uniform dissipation of static electricity on the material surface.

[0089] S4: Cardboard forming and processing S41: Gradient drying Use a multi-stage dryer to heat up to 55 °C at a heating rate of 1.0 °C / minute and dry for 20 minutes, then heat up to 75 °C and continue drying for 15 minutes. Control the relative humidity during the gradient drying process, keep it at 65% in the initial stage, and gradually reduce it to 35% in the later stage to ensure that the ionic liquid functional layer remains active during drying.

[0090] S42: Pressing and humidity adjustment Implementation of S83: Adopt a two-stage temperature-controlled cyclic pressing process - first, raise the temperature from room temperature to 68°C at a rate of 2.5°C per minute and hold for 75 seconds, then cool to 38°C at a rate of 2.5°C per minute and hold for 60 seconds, and then repeat the same temperature cycle once. The total time is controlled within 4.5 minutes. Press at a pressure of 1.0 MPa, and use a precision temperature control system to ensure the accuracy of the heating and cooling rates. This special temperature control cycle prompts the rearrangement of polymer chain segments in the composite to form a dynamic hydrogen bond network, providing electrostatic self-healing ability. After pressing, place the cardboard in an environment with a relative humidity of 50% and a temperature of 23°C for 5 hours to ensure the stable formation of the dynamic hydrogen bond network.

[0091] S43: Die-cutting and forming According to the design requirements, use a computer-controlled precision die-cutting machine to die-cut, score, and form the processed cardboard to obtain a finished moisture-proof and anti-static carton. An anti-static device is used during the die-cutting process to avoid damage to the functional coating caused by static electricity generated during processing. The formed carton is conditioned in a constant temperature and humidity environment for 24 hours to make the dynamic hydrogen bond network and ion distribution reach a stable state.

[0092] First, synthesize a bifunctional intelligent responsive ionic liquid [HEIM][DCA / TFSI] with a specific cation-anion ratio through bio-based raw materials. The mixed anions [DCA]⁻ / [TFSI]⁻ in the ionic liquid are mixed at a molar ratio of 8:1, providing an excellent basis for moisture-proof and conductive properties.

[0093] When preparing the functional biological carrier composite, add partially hydrophobic modified polyvinyl alcohol to the first composite, and adopt an isocyanate pre-crosslinking and mixed plasticizer system in the second composite. These additives work together to form a polymer network with dynamic response ability, providing both good mechanical strength and electrostatic self-healing function.

[0094] During the cardboard preparation process, according to different coating requirements (blade coating, spraying, or dipping), specifically adjust the viscosity of the coating solution and process parameters to ensure a uniform and stable functional coating can be obtained under various coating conditions. This flexibility enables the same formulation to adapt to different production lines and process requirements.

[0095] An innovative two-stage temperature-controlled cyclic process is adopted during the pressing process. Through the temperature cycle, the rearrangement of polymer chain segments and the formation of a dynamic hydrogen bond network are induced. This special structure can achieve the redistribution of charges through the breakage and recombination of hydrogen bonds when the electrostatic conditions change, thus achieving the effect of electrostatic self-healing.

[0096] Finally, the completed moisture-proof and anti-static carton has multiple functional layers: the internal pulp layer contains partially hydrophobic modified polyvinyl alcohol and ionic liquid complexes, providing basic moisture-proof and anti-static functions; the isocyanate-crosslinked alginate in the surface coating forms a dynamic network with ionic liquids and plasticizers, providing electrostatic self-healing function.

[0097] By adding partially hydrophobic modified polyvinyl alcohol to the first biological carrier complex, a microstructure with alternating semi-crystalline regions and amorphous regions is formed, providing space for charge storage and release, and enhancing the anti-static performance and long-term stability of the carton.

[0098] The pre-reaction of multifunctional isocyanate crosslinking agent with alginate creates a partially crosslinked three-dimensional network, providing a stable carrier environment for ionic liquids while maintaining sufficient segmental freedom, enabling ions to migrate and rearrange under the action of an electric field.

[0099] The synergistic effect of the mixed plasticizer of glycerol and tributyl citrate provides moderate segmental flexibility and molecular mobility, reducing the glass transition temperature of the polymer, and enabling the material to have good ionic migration ability and self-healing characteristics at room temperature.

[0100] The two-stage temperature-controlled cyclic pressing process promotes the rearrangement of polymer segments and ions through a temperature-induced phase change process, forming a dynamic hydrogen bond network. This network can spontaneously reorganize when subjected to electrostatic interference, quickly dissipate the accumulated charges, and achieve the electrostatic self-healing function.

[0101] The process parameters optimized according to different coating methods enable the technical solution of the present invention to adapt to various production equipment and technological processes, improving the flexibility and feasibility of industrial implementation. At the same time, the microstructural differences generated by different coating methods can meet different levels of moisture-proof and anti-static requirements.

[0102] The dense functional layer produced by the scraping coating process provides excellent physical barrier effects; the porous structure formed by the spraying process enhances the ionic migration efficiency; the impregnation process realizes all-round protection of internal and external integration. This diverse process selection provides customized solutions for different application scenarios.

[0103] The electrostatic self-healing function significantly extends the service life and durability of the protection effect of the carton, reduces the risk of electrostatic hazards to packaged items, and is particularly suitable for the long-term storage and transportation of high-precision electronic components, fine chemicals, and pharmaceutical products.

[0104] The integrated dynamic hydrogen bond network not only provides the electrostatic self-healing function but also enhances the physical and mechanical properties of the carton, improving the compressive strength, folding toughness, and tear strength, making the carton have better protection performance during logistics transportation.

[0105] The precise control of each step in the production process and the synergistic effect of additives enable the final product to exceed the simple additive effect in terms of performance, achieving the organic unity of moisture-proof, anti-static, and self-repair functions, and creating a high-performance packaging material with intelligent response characteristics.

[0106] The moisture-proof and anti-static cartons produced by this method not only meet the high-demand packaging requirements of industries such as electronics and medicine, but also have characteristics such as bio-based raw material sources and environmental friendliness, conforming to the development direction of sustainable development and green packaging.

[0107] The above are only the preferred embodiments of the present invention. It should be understood that the present invention is not limited to the form disclosed herein, should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications, and environments, and can be changed within the scope of the concept described herein through the above teachings or the technology or knowledge in related fields. Any changes and variations made by those skilled in the art without departing from the spirit and scope of the present invention shall fall within the protection scope of the appended claims of the present invention.

Claims

1. A method for producing a moisture-proof and anti-static carton, characterized in that, It includes the following steps: S1: Prepare a bifunctional intelligent responsive ionic liquid, which contains 1-hydroxyethyl-3-methylimidazolium cation [HEIM]⁺ and a mixed anion of dicyanimide / bis(trifluoromethanesulfonyl)imide [DCA]⁻ / [TFSI]⁻, where the molar ratio of [DCA]⁻ / [TFSI]⁻ is 5:1 to 9:1; S2: Compound the ionic liquid with chitosan and alginate respectively to prepare a first biological carrier complex and a second biological carrier complex; S3: Add the first biological carrier complex to the pulp to form a base cardboard by papermaking, and coat the second biological carrier complex on the surface of the cardboard to form a moisture-proof and antistatic functional layer; S4: Gradient dry, press and die-cut the cardboard to make a moisture-proof and antistatic carton.

2. The production method of a moisture-proof and anti-static carton according to claim 1, wherein: The step S1 includes: S11: React biobased methylimidazole and biobased hydroxyethyl chloride in a system with pH 8.0 - 9.

0. Preferably, use immobilized lipase (Novozyme 435, reference Biotechnol. Lett., 2019, 41:123 - 131) or potassium hydroxide as a catalyst, and react at 35 - 45 °C for 8 - 12 hours to generate 1-hydroxyethyl-3-methylimidazolium chloride; S12: After centrifuging (6000 rpm, 15 minutes) the product of step S11 to separate the catalyst, mix it with lithium dicyanimide and lithium bis(trifluoromethanesulfonyl)imide according to a predetermined molar ratio, and react with ultrasonic assistance at 20 - 50 kHz for 30 - 60 minutes in acetonitrile / water (volume ratio 2:1 to 4:1, total salt concentration 0.2 - 0.5 mol / L); S13: Centrifuge the reaction solution in sequence, purify it by organic solvent / water two-phase extraction, and freeze-dry it for 12 - 36 hours to obtain [HEIM][DCA / TFSI] ionic liquid with a purity of not less than 95%.

3. A method for producing a moisture-proof and anti-static carton according to claim 1, characterized in that: The step S2 includes: S21: Dissolve modified chitosan in a 1 - 3% acidic solution, mix it with the ionic liquid according to a mass ratio of 1:1 to 1:3, add 3 - 8% polyvinylpyrrolidone as a compatibilizer, and stir at 50 - 70 °C for 2 - 4 hours to prepare the first biological carrier complex; S22: Mix alginate and the ionic liquid according to a ratio of 1:1 to 1:2, add 5 - 10% nonionic crosslinking agent, and add 1 - 5% nano enhancer, and crosslink at room temperature for 4 - 6 hours to prepare the second biological carrier complex.

4. A method for producing a moisture-proof and anti-static carton according to claim 1, characterized in that: The step S3 includes: S31: Add the first complex to the pulp (pH 6.5 - 7.5) at 1 - 3%, and simultaneously add 0.5 - 1.5% carboxymethyl cellulose and 0.2 - 0.5% cationic starch; S32: Use segmented vacuum dewatering during papermaking, with an initial negative pressure of 10 - 15 kPa and a final negative pressure of 20 - 25 kPa; S33: Mix the second complex with 15 - 25% polyethylene glycol template agent (molecular weight 6,000 - 12,000), adjust the viscosity according to the coating method, apply it to the surface of the cardboard, and the coating amount is 30 - 80 g / m²; S34: Immerse the coated cardboard in an alkaline solution with a pH of 8.5 - 10.0 for 8 - 15 minutes, immediately rinse it with a weak acid solution (pH 4.0 - 5.5) for 5 - 15 seconds for neutralization, and then thoroughly rinse it with deionized water to form a nanoporous network with pore sizes of 20 - 50 nm.

5. A method for producing a moisture-proof and anti-static carton according to claim 1, characterized in that: The said step S4 includes: S41: Dry at a heating rate of 0.5 - 1.5 °C / minute to 50 - 60 °C for 15 - 25 minutes, and then dry at 70 - 80 °C for 10 - 20 minutes; S42: Under a pressure of 0.5 - 1.5 MPa, hot press at 55 - 70 °C for 1 - 3 minutes (adjust the temperature according to the cardboard thickness and fiber composition), cool to 35 - 45 °C at a rate not exceeding 3 °C / minute, and then balance in an environment with a relative humidity of 40 - 60% for 4 - 6 hours; S43: Die-cut the treated cardboard to make a moisture-proof and anti-static carton.

6. A method for producing a moisture-proof and anti-static carton according to claim 1, characterized in that: A multi-level protection structure is formed through the following steps: S61: Add 0.5 - 1.5% of an amino-modified fluorosilane surface energy regulator (such as N-(3-trimethoxysilylpropyl)ethylenediamine) to the coating solution, control the coating speed at 6 - 10 m / min, and promote the directional migration of [TFSI]⁻ to the surface through the surface energy gradient formed during the solvent evaporation process; S62: Add 0.5 - 1.5% of carboxymethyl cellulose and 0.2 - 0.4% of cationic starch to the pulp, control the beating degree at 30 - 40 °SR, and promote the formation of a continuous conductive network of [DCA]⁻ in the middle layer; S63: Control the pulp temperature at 30 - 40 °C, the stirring speed at 150 - 200 rpm, and add 0.2 - 0.5% of a dispersant to improve the uniform distribution of the ionic liquid complex between the fibers.

7. A method for producing a moisture-proof and anti-static carton according to claim 1, characterized in that: Humidity response is achieved through the following steps: S71: Control the molar ratio of [DCA]⁻ / [TFSI]⁻ to be 6:1 to 8:1 in the said step S1; S72: Add 3 - 8% of polydimethylsiloxane (viscosity 500 - 2000 cSt) and 2 - 5% of polyether-modified polysiloxane as a compatibilizer in the said step S22, and use ultrasonic dispersion for pre-mixing for 10 - 15 minutes to ensure uniform dispersion of the components; S73: Control the coating thickness to be 15 - 25 μm and the density to be 0.8 - 1.2 g / cm³, and implement slow gradient drying in step S41 to form a humidity-sensitive ionic distribution structure.

8. A method for producing a moisture-proof and anti-static carton according to claim 1, characterized in that: Electrostatic self-repair is achieved through the following steps: S81: Add 5 - 10% of partially hydrophobic modified polyvinyl alcohol (acetylation degree 5 - 15%, molecular weight 85,000 - 120,000) in the said step S21; S82: First add 1 - 3% of a polyfunctional isocyanate cross-linking agent in the said step S22 to pre-react with alginate for 30 - 60 minutes, and then add 3 - 5% of glycerol and 1 - 3% of tributyl citrate as a mixed plasticizer; S83: In the step S42, a two-stage temperature control cycle is adopted: heating from room temperature to 65 - 70°C at a rate of 2 - 3°C per minute and holding for 60 - 90 seconds, then cooling to 35 - 40°C at a rate of 2 - 3°C per minute and holding for 60 seconds, repeating once, and controlling the total time within 5 minutes to efficiently form a dynamic hydrogen bond network.

9. A method for producing a moisture-proof and anti-static carton according to claim 1, characterized in that: In the step S3, adjust the process parameters according to different coating methods: S91: When scraping coating, the viscosity of the coating liquid is controlled at 500 - 1000 mPa·s, and the scraping gap is 100 - 200 μm; S92: When spraying coating, the viscosity of the coating liquid is controlled at 100 - 250 mPa·s (the fluidity can be adjusted by adding 5 - 10% ethanol or isopropanol), the spraying pressure is 0.2 - 0.4 MPa, and the nozzle distance is 150 - 250 mm; S93: When dipping coating, the viscosity of the coating liquid is controlled at 300 - 600 mPa·s, the dipping time is 15 - 45 seconds, and the pulling speed is 3 - 8 mm / s.

Citation Information

Patent Citations

  • A kind of production method of pulp with antistatic properties

    CN106638079B

  • A waterproof and antistatic corrugated cardboard

    CN111778758B

Cited By

  • Electronic carrier tape body paper capable of effectively controlling static electricity and preparation method

    CN122406602A